2016
DOI: 10.5380/rf.v46i3.39529
|View full text |Cite
|
Sign up to set email alerts
|

Efeito responsivo de mudas de paricá ao estresse hídrico

Abstract: The present study objective was identifying mechanisms of response to water deficit of paricá seedlings. The experiment was conducted in a greenhouse, in 8-liter pots, with substrate consisting of soil (dystrophic RedYellow Latosol), in randomized block design, with five different irrigations based on the evapotranspiration of the plants (20, 40, 60, 80 and 100%), with six replications. The plants were irrigated daily, with a water volume corresponding to 100% of the evapotranspired water, and, at 90 days afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…This ratio is used to assess the quality of forest seedlings, because, in addition to reflecting the accumulation of reserves, it ensures greater resistance and better fixation in the soil [ 27 ]. The occurrence of water deficit in the substrates tends to limit the growth of tree seedlings in terms of diameter and height and modify the ideal H/D ratio for a given species [ 28 ]. However, the variations in the H/D ratio observed in this study were not enough to provide signs of etiolation in the seedlings.…”
Section: Resultsmentioning
confidence: 99%
“…This ratio is used to assess the quality of forest seedlings, because, in addition to reflecting the accumulation of reserves, it ensures greater resistance and better fixation in the soil [ 27 ]. The occurrence of water deficit in the substrates tends to limit the growth of tree seedlings in terms of diameter and height and modify the ideal H/D ratio for a given species [ 28 ]. However, the variations in the H/D ratio observed in this study were not enough to provide signs of etiolation in the seedlings.…”
Section: Resultsmentioning
confidence: 99%
“…amazonicum (paricá) and other species, but there are no studies to confirm this. Duarte et al (2016) reported that S. parahyba var. amazonicum plants when submitted to water deficit, with subsequent water replenishment, showed reduction in the number of leaves, stem diameter, plant height, and, of course, total biomass, as response to maintain the internal water, indicating low ability to tolerate stress.…”
mentioning
confidence: 99%
“…The seeds came from the Aimex Laboratory of Seeds and Seedlings of the Amazon Forest Species. Dormancy break procedure was applied to the seeds, according to the methodology proposed by Duarte et al (2016). Three seeds were sown in each pot and thinning was carried out 30 days after emergence (DAE).…”
mentioning
confidence: 99%
See 2 more Smart Citations